Pia Arke - Arke, Pia 1958-2007; Jørgensen, Lærke Rydal 1986-; Kold, Anders (Louisiana Museum of Modern Art, 2021)
Central to the multimedia oeuvre of Pia Arke (1958-2007) was the artist's dual ethnicity in Greenland and Denmark, excavated in video works, collaged maps and landscape photographs that addressed themes of exploration, the complexities of ethnicity. Famed for her film Arctic Hysteria, Arke died of cancer at 48, and her work has only gained recognition over the past decade. With reproductions and essays, this volume introduces her to a wider audience. Kim Leine discusses themes of mortality; Darren Almond charts Arke's depictions of the landscapes of Greenland; Minik Rosing looks at spirituality in relation to Greenland; Laura Smith examines "Arctic hysteria"; Erik Steffensen recounts the artist's early years; Stefan Jonsson gives a biographical portrait; Erik Gant delves into the relationship between art and reality; Jessie Kleemann is interviewed about Arke's legacy; and the exhibition's curator, Anders Kold, explores Arke's motifs of body and map.
Impressum: The catalogue is published on the occasion of the exhibition "Pia Arke. Dream and Repression", Louisiana Museum of Modern Art, Humlebæk, 15 July 2021-2 January 2022; Kunsten Museum of Modern Art, Aalborg, 14 January-18 April 2022; Kunstmuseum Brandts, Odense, 12 May-25 September 2022
Keywords: Arke, Pia -- 1958-2007; Ausstellungskatalog -- Louisiana Museum of Modern Art -- 15.07.2021-02.01.2022 -- Humlebaek; Ausstellungskatalog -- Kunsten - Museum of Modern Art -- 14.01.2022-18.04.2022 -- Aalborg; Ausstellungskatalog -- Brandts Odense -- 12.05.2022-25.09.2022 -- Odense